Performance Augmenting of a Vertical Axis Wind Turbine using Adaptable Convergent Ducting System - Jadallah, Abdullateef A.; Farag, Sahar R.; Hamdi, Jinan D. (Al-Khwarizmi Engineering Journal, 2018)
Developments are carried out to enhance the performance of vertical axis wind turbines (VAWT). This paper studies the performance of the ducted wind turbine with convergent duct (DAWT). Basically, the duct technique is utilized to provide the desired wind velocity facing the turbine. Methodology was developed to estimate the decisive performance parameter and to present the effect of the convergent duct with different inlet angles. The ducted wind turbine was analyzed and simulated using MATLAB software and numerically using ANSYS-Fluent 17.2. Result of both approaches were presented and showed good closeness for the two cases of covering angles 12  and 20 respectively. Results also showed that the convergent duct with an inlet angle 12   and 20  improved the coefficient of performance at a specified tip speed ratio by 25.8% and 33.33% respectively in the productivity of wind turbine.